Identification of ABA-Mediated Genetic and Metabolic Responses to Soil Flooding in Tomato (Solanum lycopersicum L. Mill) - De Ollas, Carlos; González-Guzmán, Miguel; Pitarch, Zara; Matus, José Tomás; Candela, Héctor; Rambla, José Luis; Granell, Antonio; Gómez-Cadenas, Aurelio; Arbona, Vicent (Frontiers in Plant Science, 2021)
Soil flooding is a compound abiotic stress that alters soil properties and limits atmospheric gas diffusion (O2 and CO2) to the roots. The involvement of abscisic acid (ABA) in the regulation of soil flooding-specific genetic and metabolic responses has been scarcely studied despite its key importance as regulator in other abiotic stress conditions. To attain this objective, wild-type and ABA-deficient tomato were subjected to short term (24 h) soil waterlogging. After this period, gas exchange parameters reduced in wild type but not in ABA-deficient plants that always had higher E and gs. Transcript and metabolite alterations were more intense in waterlogged tissues, with genotype-specific variations. Waterlogging reduced ABA levels in roots while induced PYR/PYL/RCAR ABA receptors and ABA-dependent transcription factor transcripts which induction was less pronounced in the ABA-deficient genotype. Ethylene/O2-dependent genetic responses (ERFVIIs, plant anoxia survival responses and genes involved in the N-degron pathway) were induced in hypoxic tissues independently of the genotype. Interestingly, genes encoding a nitrate reductase and a phytoglobin involved in NO biosynthesis and scavenging and ERFVII stability, were induced in waterlogged tissues but to a lower extent in ABA-deficient tomato. At metabolic level, flooding-induced accumulation of Ala was enhanced in ABA-deficient lines following a differential accumulation of Glu and Asp in both hypoxic and aerated tissues, supporting their involvement as sources of oxalacetate to feed TCA cycle in waterlogged tissues and constituting a potential advantage upon long periods of soil waterlogging. Promoter analysis of upregulated genes indicated that the production of oxalacetate from Asp via Asp oxidase, energy processes such as acetyl-CoA, ATP and starch biosynthesis and the lignification process were likely subjected to ABA regulation. Taken together, these data indicate that ABA depletion in waterlogged tissues acts as a positive signal inducing several specific genetic and metabolic responses to soil flooding.